An EEG study on the somatotopic organisation of sensorimotor cortex activation during action execution and observation in infancy - Carina C.J.M. de Klerk; Mark H. Johnson; Victoria Southgate (Developmental Cognitive Neuroscience, 2015)
Previous studies have shown that sensorimotor cortex activation is somatotopically-organised during action execution and observation in adulthood. Here we aimed to investigate the development of this phenomenon in infancy. We elicited arm and leg actions from 12-month-old infants and presented them, and a control group of adults, with videos of arm and leg actions while we measured their sensorimotor alpha suppression using EEG. Sensorimotor alpha suppression during action execution was somatotopically organised in 12-month-old infants: there was more suppression over the arm areas when infants performed reaching actions, and more suppression over the leg area when they performed kicking actions. Adults also showed somatotopically-organised activation during the observation of reaching and kicking actions. In contrast, infants did not show somatotopically-organised activation during action observation, but instead activated the arm areas when observing both reaching and kicking actions. We suggest that the somatotopic organisation of sensorimotor cortex activation during action observation may depend on infants’ understanding of the action goal and their expectations about how this goal will be achieved.